Two foci of the ellipse are ( 2 - √3) and moves clockwise three fourth is ( 2 + √3).
As given in the question,
Given equations are :
x = 1 + sin(t)
⇒ sin(t) = (x - 1)
y = 6 + 2cos(t)
⇒cos(t) = (y - 6)/2
We know that,
sin²t + cos²t = 1
Substitute the value of sin(t) and cos(t) we get,
(x - 1)²/ 1² + (y - 6)²/ 2² = 1
Standard Equation of the ellipse is:
( x -h)²/b² + (y - k)²/a² = 1
Center of the ellipse = (h , k)
(h , k) = (1, 6)
here b = 1 and a = 2
'c' is the distance from focus to the center
c = √a² - b²
= √4 -1
= √3
Therefore , two foci for the given ellipse are ( 2 - √3) and moves clockwise three fourth is ( 2 + √3).
Learn more about ellipse here
brainly.com/question/14281133
#SPJ4